Bonjour! je ne comprends pas cet exercice, merci de m'aider.


f(1) = 2x² - 3x + 6
f(-1) = 2x² - 3x + 6
f(2) = 2x² - 3x + 6

f(1) = 3 sur (x + 5)
f(-1) = 3 sur (x + 5)
f(2) = 3 sur (x + 5)

f(1) = (x-3)² + 2
f(-1) = (x-3)² + 2
f(2) = (x-3)² + 2

f(1) = 3 sur x + (5)
f(-1) = 3 sur x + (5)
f(2) = 3 sur x + (5)

1

Réponses

2014-09-08T19:52:23+02:00
F(1) = 2 x 1² -3 x 1 + 6 = 2 -3 + 6 = 5
f(-1) = 2 x (-1)² -3 x (-1) + 6 = 2 - (-3) + 6 = 11
f(2) = 2 x 2² - 3 x 2 +6 = 2 x 4 -6 + 6 = 8
f(1) = 3 sur (1 +5) = 3 sur 6 ou 0.5
f(-1) = 3 sur (-1+5) = 3 sur 4 ou 0.75
f(2) = 3 sur (2 +5) = 3 sur 7
f(1) = (1-3)² + 2 = -2² + 2 = -4 + 2 = -2
f(-1) = (-1 - 3)² + 2 = -4² + 2 = -16 + 2 = -14
f(2) = (2 - 3)² +2 = -1² +2 = -1 + 2 = 1
f(1) = 3 sur 1 + 5 = 3 sur 6 ou 0.5
f(-1) = 3 sur -1 + 5 = 3 sur 4 ou 0.75
f(2) = 3 sur 2 + 5 = 3 sur 8